Elevated Numbers of HIV-Specific Poly-Functional CD8+ T Cells With Stem Cell-Like and Follicular Homing Phenotypes in HIV-Exposed Seronegative Individuals - Sivasankaran Munusamy Ponnan; Sivasankaran Munusamy Ponnan; Kannan Thiruvengadam; Sujitha Kathirvel; Janani Shankar; Akshaya Rajaraman; Manikannan Mathaiyan; Thongadi Ramesh Dinesha; Selvamuthu Poongulali; Shanmugam Saravanan; Kailapuri Gangatharan Murugavel; Soumya Swaminathan; et al. (Frontiers in Immunology, 2021)
HIV-specific CD8+ T cells are known to play a key role in viral control during acute and chronic HIV infection. Although many studies have demonstrated the importance of HIV-specific CD8+ T cells in viral control, its correlation with protection against HIV infection remains incompletely understood. To better understand the nature of the immune response that contributes to the early control of HIV infection, we analyzed the phenotype, distribution and function of anti-viral CD8+ T cells in a cohort of HIV-exposed seronegative (HESN) women, and compared them with healthy controls and HIV-infected individuals. Further, we evaluated the in vitro viral inhibition activity of CD8+ T cells against diverse HIV-1 strains. We found that the HESN group had significantly higher levels of CD8+ T cells that express T-stem cell-like (TSCM) and follicular homing (CXCR5+) phenotype with more effector like characteristics as compared to healthy controls. Further, we observed that the HESN population had a higher frequency of HIV-specific poly-functional CD8+ T cells with robust in vitro virus inhibiting capacity against different clades of HIV. Overall, our results demonstrate that the HESN population has elevated levels of HIV-specific poly-functional CD8+ T cells with robust virus inhibiting ability and express elevated levels of markers pertaining to TSCM and follicular homing phenotype. These results demonstrate that future vaccine and therapeutic strategies should focus on eliciting these critical CD8+ T cell subsets.